Pengaruh Insentif Pajak Dan Digitalisasi Pajak Terhadap Penerimaan Pajak Penghasilan Badan Di KPP Pratama Jakarta Pasar Rebo - Apriyani, Haisa; Harjo, Dwikora (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The tax revenue data of the KPP Pratama Jakarta Pasar Rebo over the past few years reflects a downward trend, indicating the impact of limited accessibility and transparency of tax incentive information, as well as the lack of readiness and accessibility to technology among taxpayers, hindering optimal utilization of tax incentives and tax digitization adoption. This study aims to identify and analyze the impact of tax incentives on tax revenue, the impact of tax digitization on tax revenue, and the combined impact of tax incentives and tax digitization on tax revenue at the KPP Pratama Jakarta Pasar Rebo. The research employs a descriptive quantitative method with a population of all corporate taxpayers who filed tax returns in 2022 at the KPP Pratama Jakarta Pasar Rebo, totaling 966 corporate taxpayers. A sample size of 97 respondents was determined based on Arikunto's theory, which suggests sampling 10% of the population. Based on the research findings, it is concluded that Tax Incentives partially influence tax revenue positively by 50.3% at the KPP Pratama Jakarta Pasar Rebo, while Tax Digitization partially influences tax revenue positively by 57.7%. Furthermore, Tax Incentives and Tax Digitization together significantly influence tax revenue positively by 60.8% at the KPP Pratama Jakarta Pasar Rebo. To enhance tax revenue at the KPP Pratama Jakarta Pasar Rebo, it is recommended to improve tax incentives by refining incentive procedures, enhancing communication and transparency, and encouraging active participation of corporate taxpayers in providing accurate data to minimize tax calculation errors.